VAGINAL CANDIDOSIS. ALTERNATIVES OF PHARMACOTHERAPY - L. O. Makarov; N. A. Sheshukova (IRBIS LLC, 2016)
Vaginal candidosis is very common disease in patients with immunodeficiency. As vaginal candidosis is often associated with other dysbiotic disturbances of vaginal microcenosis medications with wide spectrum of activities should be indicated for treatment of candidainfections. To assess fenticonazol therapeutical efficacy in treatment of chronic vaginal candidosis 32 patients in age of 22-42 years were examined. Inclusion criteria were: presence of history of 4 or more episodes of vaginal candidosis in an year, absence of sexually transmitted infections at the moment of examination. All patients were assigned to fenticonazol 600 mg for vaginal administration, and to its repeated dose (600 mg) in three days. At the second step of treatment medications normalizing the functions of immune system (interferons) were indicated. The results demonstrated high clinical and microbiological efficacy of feticonazol in chronic vaginal candidosis treatment.